Exploring Accountability and Transparency in Government Agency Management: A Literature Review - Irawati, Syati; Hayat, Atma; Juniar, Asrid; Handayani, Sri Astuti (Ilomata International Journal of Management, 2024)
Public bureaucratic practices are frequently criticized for being impolite, unfriendly, discriminatory, and for having service systems that are non-transparent, complicated, and do not guarantee certainty in terms of time and costs. These issues arise from a lack of transparency and accountability in public service implementation. Transparency involves the freedom to access information, while accountability ensures that activities are carried out responsibly and answerable to the public. This research explores the relationship between accountability and transparency in government agency management through a literature review. The study analyzes 30 journals from state and private universities, published between 2018 and 2023, to understand their impact on government performance. Data was collected from Google Scholar using the keywords "accountability and transparency." Strict criteria and limitations were applied to ensure the relevance and suitability of the data for this research. The findings emphasize the importance of accountability and transparency in improving the performance of government entities at various levels, including regional, city, and village governments, as well as organizations. These concepts are crucial for addressing issues related to performance, finance, and budget management. The study highlights the need for further research to explore these relationships in depth and to develop frameworks for better public service delivery. By integrating accountability and transparency into government operations, public trust can be restored, and the efficiency and effectiveness of public services can be significantly enhanced. This literature review serves as a reference for future studies and practical applications aimed at improving the management and performance of government agencies and organizations.